Natalizumab treatment during pregnancy - effects on the neonatal immune system - Rudolph, Henriette; Weber, Claudia Ellen; Schroten, Horst; Tenenbaum, Tobias (Acta neurologica Scandinavica, 2013)
Background: Pregnancies in women with severe relapsing-remitting multiple sclerosis treated with natalizumab constitute a major challenge, because withdrawal of the drug may cause relapses but continuation might have unknown effects on the infantile immune system. Aims of the study To identify the impact of maternal natalizumab treatment during pregnancy on basic immune functions of the newborn. Methods Basic immunological testing and assessment of the chemotaxis rate of freshly isolated T lymphocytes in the presence and absence of CXCL12 was performed in two neonates, whose mothers were treated with natalizumab until the 34th week of pregnancy (pw). Results Both children had an uneventful birth. However, a reduction in the CXCL12-induced T-cell chemotaxis was found in both children. In contrast, the chemotaxis rate of unstimulated T lymphocyres was not altered. The distribution of the lymphocyte subpopulations was investigated only in case 1 and was normal. Conclusions Here, we present to our knowledge the first assessment of T lymphocytes chemotaxis rate in two natalizumab-exposed newborns. A significant reduction in the CXCL12-induced chemotaxis rate of T lymphocytes has been observed and may compromise host defence function in early life. More clinical and immunological data on natalizumab-exposed neonates are warranted.
Gesehen am 18.06.2018
First published: 05 September 2012